Labor market shocks and their impacts on work and schooling: evidence from urban Mexico - Skoufias, Emmanuel; Parker, Susan W. (International Food Policy Research Institute, 2002)
The authors use individual observations from a panel of families during the period of the peso crisis in Mexico to investigate whether and how labor market shocks, as proxied by changes in the gender- and age-specific unemployment rates in the metropolitan area of the household, affect the intertemporal time allocation of adult members and children. Their findings suggest that significant added-worker effects are in operation, especially for adult females of poorer households and in some cases children. The same shocks also increase significantly the probability that children do not continue school in the next year. The paper also presents evidence suggesting differential treatment based on the sex of children within families.